Diagnóstico diferencial do vírus da necrose hipodérmica e hematopoiética na forma ativa com base na escolha do gene e transcrição reversa por meio de PCR - Teixeira, M. A.; Cruz, J. E. F.; Vieira, P. R. N.; Branco, I. R. C.; Costa, F. H. F.; Rádis-Baptista, G. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
The Pacific whiteleg shrimp Litopenaeus vannamei (Penaeidae) is one of the most important cultivated species in world aquaculture. In Brazil, the Northeastern states are home to the main shrimp producers. As shrimp aquaculture has expanded and intensified, diseases have progressively become one of the most serious threats to this industry. Infectious hypodermal and hematopoietic necrosis virus (IHHNV) is an enzootic viral agent in Brazilian shrimp farms. These viruses are usually diagnosed by histological methods. However,to detect sub-clinical or acute IHHNV infection, more refined methods based on molecular techniques have been utilized. We found that by using “universal” primers and a single-step PCR diagnostic test, it was difficult to distinguish between non-infective forms of the virus and active IHHNV. Detection of IHHNV was more accurate when we used two alternative molecular strategies, namely 1) single-step PCR amplification based on gene choice and 2) reverse transcription coupled with PCR. This communication presents the results of our strategy that can be adaptable for routine diagnostic programs in shrimp culture for detecting the presence of active IHHN virus.